Characteristics of the mud shale reservoirs in coal-bearing strata and resources evaluation in the eastern margin of the Ordos Basin, China. Issue 2 (March 2020) - Chen, Yue; Ma, Dongmin; Xia, Yucheng; Guo, Chen; Yang, Fu; Shao, Kai
As the co-exploration and co-production of unconventional gas have become a new trend of the unconventional gas exploration and development in the eastern margin of the Ordos Basin, this study focuses on the distribution, pore characteristics, geochemical properties, and mineral composition of the mud shale in the coal-bearing strata. The results show that the mud shale in the coal-bearing strata is distributed relatively stably with an average cumulative thickness of 77.60 m and a buried depth of 200–2400 m, increasing from east to west. The total organic carbon content of mud shale is relatively high, ranging from 0.14% to 39.9%, and the thermal maturity ranges from 0.23% to 2.49%, affected by both buried depth and magmatic intrusion. The organic matter type of the mud shale is dominated by type III, favorable for gas generation. The mineral composition of mud shale is mainly clay minerals and quartz, with low brittle minerals content (averaging 30.34%) and high kaolinite content (averaging 59.23%). Pores and micro-fissures are relatively developed in the mud shale, dominated by intergranular pores, organic pores, and the micro-fissures developed between brittle mineral crystals, within crystals and between clay mineral particles, with a porosity of 1.05%–1.59% and a permeability of 0.001–0.142 (×10 −3 µm 2 ). The specific surface area of pores in mud shale is 12.31–28.99 m 2 /g, and the total pore volume is 0.0146–0.0483 cm 3 /g. Mesopores and micropores (mainly slit shaped pores) provide the main pore volume of mud shale, and micropores contribute most of the specific surface area. The controlling factors on pore development include the total organic carbon, thermal maturity, and inorganic minerals composition. The total amount of shale gas resources is 2.49 × 10 12 m 3, and the Linxian-Xingxian area and Shilou-Daning area are the potential favorable zones for shale gas exploration and development.